Pengaruh Kepemimpinan, Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Aston Graphindo Indonesia - Annisa, Nenden Nur, Nur Achmad, S.E., M.Si (2015)
The aim of this study was to determine the effect of leadership, work environment and work motivation on employee performance of PT. Aston Graphindo Indonesia. This study also aims to determine simultaneously the influence of three independent variables on the dependent variable and to determine which variable peling dominant influence among the three independent variables on the dependent variable. This type of research is a quantitative research, with a population of all employees of PT. Aston Graphindo Indonesia which amounted to 92 employees as the population, with a sample of 49 people. Sampling using simple random sampling or simple random. Research data collection techniques through a questionnaire with Likert scale. Based on calculations from SPSS 20:00 t test variables obtained significant leadership at 0.053 <0.10 H_0 H_a rejected and accepted, the work environment variables significant at 0.075 <0.10 H_0 H_a accepted and rejected and no significant motivation variable with a value of 0.740> 0 , 10 H_0 H_a accepted and rejected. F-test probability of significant 0,000 <0.05 H_0 H_a rejected and accepted, so in this study independent variables jointly affect the dependent variable. The coefficient of determination R ^ 2 was obtained a yield of 0.286 means that the variables of leadership, work environment and work motivation may explain the variable performance of employees is 0.286, or 28.6%, the rest can be explained by other variables that are not included in the model. Keywords: Employee Performance, Leadership, Work Environment and motivation of employees.